2014
DOI: 10.1109/tns.2014.2362872
|View full text |Cite
|
Sign up to set email alerts
|

RF Performance of Proton-Irradiated AlGaN/GaN HEMTs

Abstract: AlGaN/GaN high electron mobility transistors (HEMTs) irradiated with 1.8-MeV protons show more relative degradation in RF power/current gain, cutoff frequency , and maximum oscillation frequency than DC transconductance. These result from radiation-induced increases in fast bulk and surface trap densities, as well as increasing impedance mismatch at high frequencies with increasing proton fluence.-rich MBE devices show less degradation in DC transconductance, but more degradation in RF gain than Ga-rich device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 23 publications
(34 reference statements)
2
16
0
Order By: Relevance
“…30,35,36 The threshold voltage shifts were found to be the highest for N-rich MBE growth, considerably lower for Ga-rich MBE growth, and the lowest for NH 3 -MBE and MOCVD growth (both characterized by N-rich conditions and the abundance of hydrogen). In a comparison of HEMTs grown only by MBE under Ga-rich or ammonia -rich conditions, while there was no difference in pinch-off voltage change with proton fluence, 45 there were significant differences in transconductance as shown in Figure 10. 45 The NH 3 -rich devices showed lower degrees of degradation in transconductance with increasing proton fluence and the 1/ f noise of the devices increased with increasing fluence.…”
Section: Summary Of Radiation Effects In Ganmentioning
confidence: 97%
See 2 more Smart Citations
“…30,35,36 The threshold voltage shifts were found to be the highest for N-rich MBE growth, considerably lower for Ga-rich MBE growth, and the lowest for NH 3 -MBE and MOCVD growth (both characterized by N-rich conditions and the abundance of hydrogen). In a comparison of HEMTs grown only by MBE under Ga-rich or ammonia -rich conditions, while there was no difference in pinch-off voltage change with proton fluence, 45 there were significant differences in transconductance as shown in Figure 10. 45 The NH 3 -rich devices showed lower degrees of degradation in transconductance with increasing proton fluence and the 1/ f noise of the devices increased with increasing fluence.…”
Section: Summary Of Radiation Effects In Ganmentioning
confidence: 97%
“…In a comparison of HEMTs grown only by MBE under Ga-rich or ammonia -rich conditions, while there was no difference in pinch-off voltage change with proton fluence, 45 there were significant differences in transconductance as shown in Figure 10. 45 The NH 3 -rich devices showed lower degrees of degradation in transconductance with increasing proton fluence and the 1/ f noise of the devices increased with increasing fluence. Density functional theory calculations showed that N vacancies and Ga-N divacancies lead to enhanced noise in these devices.…”
Section: Summary Of Radiation Effects In Ganmentioning
confidence: 97%
See 1 more Smart Citation
“…Displacement-related point defects are considered the primary damage mechanism that influences device performance in proton-irradiated InP HEMTs. [12,13,20] Energetic protons transfer part of their kinetic energy to the lattice atoms through non-ionizing energy loss (NIEL). This energy displaces atoms from their lattice sites and creates charged defect centers.…”
Section: Vacancy Profilementioning
confidence: 99%
“…Typical features are the positive shift of threshold volt-age, degradation of transconductance, current, operating frequency, and gain. [11][12][13][14][15][16][17][18] Besides, the related literature demonstrates that a large value of conduction band offset correlates with greater tolerance of radiation damage. [19,20] However, there are few studies on the proton irradiation of InP HEMTs.…”
Section: Introductionmentioning
confidence: 99%